Developing Shanghai underground pedestrian system under urbanization: mobility, functionality and equity - Cui, Jianqiang; Allan, Andrew; A. P. Taylor, Michael; Lin, Dong (Journal of Architecture and Urbanism, 2013)
Shanghai is being transformed through a process of rapid urbanization. Urbanization has the effects of increasing urban population and the income levels of residents as well as changing the structure of transportation. Under the background, from the 1980s, Shanghai has increasingly built and extended underground pedestrian systems (UPS) within central areas to complement pedestrian networks. UPS have significantly affected urban life in Shanghai under the decades of development but to date, research on UPS usage and perceptions of UPS users has been lacking. This research conducted an on-the-spot survey in Shanghai’s UPS in People’s Square, Jing’an Temple and Xujiahui areas. Investigation through observation, face to face questionnaires and interviews generated qualitative and quantitative findings on the usage characteristics and perceptions of UPS users. The discussion focused on social usage and equity and the functionality of UPS. It revealed defects in the design and management of Shanghai’s UPS, including deficiencies with regard to consideration of the elderly, disabled groups, management of homeless people, the range of merchandise categories and orientation (i.e. way-finding) systems. This research is a significant contribution to enriching knowledge and providing insights into the performance of UPS in a developing country under rapid urbanization.